REDESIGN OF PIKACHU CASUAL BACK TO SCHOOL SHOES SAMPLES AT PT PRIMARINDO ASIA INFRASTRUCTURE Tbk BANDUNG - Zain Azmi Amanullah; Anwar Hidayat (Politek ATK Yogyakarta Press, 2022)
Pikachu shoes model (back to school) are casual shoes produced by PT Primarindo Asia Infrastructure Tbk. by using the Tomkins brand for the needs of school and sports activities. Results of the observations, a problem was found, namely the discomfort after being tested for walking activities. The purpose of this study is to identify the problem of discomfort in the shoe and find a solution to repair. Problem solving method used is by conducting design experiments based on ergonomic aspects of shoes, while in data collection using observation methods, interviews, documentation and literature studies. The result obtained is that the initial design of the shoe uses an inappropriate upper and bottom material, namely the upper lacks good air circulation and the outsole material is less elastic and heavy. Design experiments were carried out using mesh materials on the upper and changes in the shape of the outsole design using phylon material in combination rubber on the bottom. Economically, the calculation of the cost increase of 15% is obtained, and it is still in the category of allowing it to be marketed because it still meets the feasibility of the production cost budget.